African Women, ICT and Neoliberal Politics : The Challenge of Gendered Digital Divides to People-Centered Governance - Zerai, Assata; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
How can we promote people-centered governance in Africa? Cell phones/ information and communications technology (ICT) are shown to be linked to neoliberal understandings of more democratic governance structures, defined by the Worldwide Governance Indicators as: the rule of law, corruption-control, regulation quality, government effectiveness, political stability/no violence, and voice and accountability. However, these indicators fall short: they do note emphasize gender equity or pro-poor policies.Writing from an African feminist scholar-activist perspective, Assata Zerai emphasizes the voices of women in two ways: (1) she examines how women's access to ICT makes a difference to the success of people-centered governance structures; and (2) she demonstrates how African women's scholarship, too often marginalized, must be used to expand and redefine the goals and indicators of democratice governance in African countries.Challenging the status quo that praises the contributions of cell phonesto the diffusion of knowledge and resultant better governance inAfrica, this book is an important read for scholars of politics and technology, gender and politics, and African Studies.
List of Figures -- List of Tables -- List of Acronyms -- -- Foreword -- Introduction: In the Traditions of Professor Victor C. Uchendu and Professor Ifi Amadiume: African Women and the Challenge of Digital Divides to People-Centered Governance -- 1. The Mobile Ecosystem and Internet Access on the African Content: Asymmetry and the Gender Digital Divide -- 2. ICT, Womens Status, and Governance in Zimbabwe -- 3. ICT, Womens Status, and Governance in Tanzania, 2010 and20152016 -- 4. ICT, Womens Status, and Governance in Malawi, 2010 and20152016 -- 5. ICT, Diffusion of Knowledge to Women, Gender Inclusive Governance, and Impacts on Womens Lives in Three African Nations -- Conclusion -- References -- Index -- References -- Biography
Includes bibliographical references and index.
Also available in print format.
Keywords: Women -- Africa -- Social conditions; Women's rights -- Africa; Sex discrimination -- Africa; Telecommunication -- Africa; Women -- Political activity -- Africa; Sex discrimination; Telecommunication; Women -- Political activity; Women -- Social conditions; Women's rights; POLITICAL SCIENCE / Political Process / Media & Internet; POLITICAL SCIENCE / Women in Politics; africa cell phones; africa politics; digital africa; gender africa; mobile africa; Electronic books